Al-Lughatul Al-'Arabiyah Kamabdai Al-Tarbawi Al-Diniy - M Fairuz Rosyid; Faliqul Isbah; Ahmad Assegaf (Indonesian Journal of Arabic Studies, 2020)
Islam is the religion of love, God has chosen Arabic as the language of this true religion. Reaching the peak of proficiency in meanings and statement; Because its wonderful melodies, how can we benefit from our understanding of generous language to feel the beauty of mercy and apply it in the life of the Islamic community in this century? In this research, I try to enumerate the reins of the Arabic statement to explain the Arabic language as the educational principle of religion, the study on Surat Al-Anbiya '107. This research starts from the Quran verse, Surat 107, with an objective approach to interpreting a verse, where all material and information becomes References from the literature on the topic, namely the Quran, and books, whether they are commentary books or other works related to the topic of this research. This endeavor is desk research so it is included in qualitative research. Data analysis was carried out three steps, namely, data reduction, data presentation and conclusions. The conclusion as follows : First, God has described Arabic as an outline, and the commentators have unanimously agreed on the meaning it meaning the most eloquent of Arabic. it also an indication that the language of the Quran exceeds the eloquence of the classical Arabic language, so God chose it in the Quran expression as the principle Religious. Secondly, the human behavior acquired is acquired through education, training and practice, so let us educate, train and practice ourselves to adhere to the Quranic behavior.